1999
DOI: 10.1021/ic981293o
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of N-Donor Ligands by the Monomeric Ferric Porphyrin N-Acetylmicroperoxidase-8

Abstract: The monomeric ferric hemepeptide from cytochrome c, N-acetylmicroperoxidase-8 (NAcMP8), retains the proximal His ligand and has a coordinated water molecule in the second axial site. It provides an opportunity for quantitatively studying in aqueous solution the coordination chemistry of an iron porphyrin with a single accessible coordination site. An examination of the dependence of the spectrophotometrically determined equilibrium constants for coordination of imidazole and cyanide as a function of pH provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 54 publications
6
39
2
Order By: Relevance
“…The formation of [Fe II (Porph)(H 2 NR)] or [Fe II (Porph)-(H 2 NR) 2 ] by autoreduction of porphyrinates with alkyl or aryl amines has also been reported previously [29]. In addition, the coordination of amines to microperoxidases has been thoroughly studied [30], and a binding constant K 1 = 8 Â 10 2 M À1 was obtained for coordination of HA in N-AcMP8. Only primary amines exhibited a redox reactivity toward microperoxidases [31], while NH 3 or imidazole were inert toward the iron(III) hemepeptide.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The formation of [Fe II (Porph)(H 2 NR)] or [Fe II (Porph)-(H 2 NR) 2 ] by autoreduction of porphyrinates with alkyl or aryl amines has also been reported previously [29]. In addition, the coordination of amines to microperoxidases has been thoroughly studied [30], and a binding constant K 1 = 8 Â 10 2 M À1 was obtained for coordination of HA in N-AcMP8. Only primary amines exhibited a redox reactivity toward microperoxidases [31], while NH 3 or imidazole were inert toward the iron(III) hemepeptide.…”
Section: Discussionmentioning
confidence: 56%
“…Time evolution leads to the formation of an intermediate of lower absorbance, red shifted from the original compound (k max = 405 nm). Both results point to a Fe III (Porph)(L)(L 0 ) complex.Bis-coordination of amines to microperoxidases, requiring the displacement of the proximal histidine, has been reported[30]. This is not the case for the reaction with HA in our reaction conditions, as1 H NMR signals of coordinated histidine were only slightly modified in the spectra recorded as a function of time (Supplementary information).3-Disproportionation mediated by [NHOH]:To account for the free-radical formation evidenced by the methylmetacrilate assay with [Fe III (TEPyP)] 5+ , the comparatively higher redox potential of [Fe III (TEPyP)] 5+ plays an essential role as it changes the scenario leading to an easy reduction of [Fe III (TEPyP)(HA) 2 ] 5+ by excess HA, with the concomitant formation of [Fe II (TEPyP)(HA) 2 ] 4+ and a radical nitrogen containing species, [NHOH] Á(Fig.…”
mentioning
confidence: 99%
“…On the other hand, the binding of primary amines to Fe(III) porphyrins has been carefully studied. It was demonstrated that there is a linear dependence of the affinity constant and the pK a of the conjugated acid of the primary amine [30]. In our case, the increase of ip for oxygen reduction correlates with a higher number of active redox centers, suggesting that the inclusion of ammonia as axial ligand promotes the required geometry to bind oxygen.…”
Section: Catalytic Activitysupporting
confidence: 48%
“…In the light of the present study, the facts that one histidine ligand to Cu B is labile and that during the enzyme cycle the tyrosine ± histidine ligand to Cu B is oxidised with a hydroxide ancillary ligand simultaneously produced [6,9,12] become most intriguing. Argument based upon the mixing of s/p electrons inherent within an imidazole [46] and the inter-ring conjugation anticipated for the tyrosine-histidine cofactor suggests its redox-state should strongly modulate its metal binding properties (Figure 8 B). The most recent evidence is that there indeed is electronic delocalisation between the rings of a histidine ± tyrosyl radical, [47] and we have shown that such inter-ring delocalisation between a ligand donor and its radical pendant can significantly alter the reactivity of a (organo-) metal centre.…”
Section: Discussionmentioning
confidence: 99%